Turkey and the Palestinian Question: The Shift of Roles in Foreign Policy. (27th September 2016) - Ertosun, Erkan
Abstract: For Turkey, which was seeking a leading role in the Middle East, the Palestinian Question became a priority in its foreign policy during the late 1990s. In this article, it is argued that the role Turkey primarily espoused in the resolution of the Palestinian Question in the period 2000–2009 has mainly been that of a communicator. Nonetheless, in times of crises between Palestine and Israel, Ankara lost its neutrality and credibility to some extent, as it shifted to the role of guardian of Palestinians and proponent of Palestine, thereby undermining its communicator role. Finally, this dilemma in Turkish foreign policy in the Palestinian Question was the fundamental impediment to Turkey's sustainable and constructive contribution to the settlement of the problem in the examined period.